Infecciones del tracto genital inferior como factor predisponente en el parto pretérmino en el Hospital General Dr. León Becerra Camacho. - Rodríguez Pérez, Josselyn Patricia (2023)
Lower genital tract infections are a major public health issue due to their impact during pregnancy and the increased risk of preterm birth. In Ecuador, preterm birth rates are increasing every year, and in 2022 they will represent 7.5%, causing complications that require hospitalization. This study aims to analyze lower genital tract infections as a predisposing factor in preterm birth. A quantitative study was carried out in the General Hospital Dr. León Becerra Camacho in the period May - November 2022. Methodology: A quantitative, deductive, non-experimental, documentary, descriptive and cross-sectional methodology was used. The information was collected through the review of pseudo-anonymized statistical data from the Hospital General Dr. León Becerra Camacho. The patients included in this study were 100 women with preterm births caused by lower genital tract infections selected under a non-probabilistic purposive sampling, among which Vaginal infections were predominant in 11.23% of the women, followed by Sexually Transmitted Infections 3.7% and Cervical Infections with 1.2% of the pregnant women; of the newborns attended, 64% were late preterm. The analysis of lower genital tract infections as a predisposing factor in preterm birth at the General Hospital Dr. León Becerra Camacho showed that there is a clear relationship between lower genital tract infections and preterm birth.